2001
DOI: 10.1001/jama.285.23.2987
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Index for 1-Year Mortality in Older Adults After Hospitalization

Abstract: Our prognostic index, which used 6 risk factors known at discharge and a simple additive point system to stratify medical patients 70 years or older according to 1-year mortality after hospitalization, had good discrimination and calibration and generalized well in an independent sample of patients at a different site. These characteristics suggest that our index may be useful for clinical care and risk adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
312
1
22

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 583 publications
(362 citation statements)
references
References 37 publications
27
312
1
22
Order By: Relevance
“…Among the 304 readmissions, the median (IQR) time to readmission was 11 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) days. The most common readmission diagnoses by CCS Level 3 category were congestive heart failure, pneumonia, coronary atherosclerosis without acute myocardial infarction, cardiac dysrhythmias, and obstructive chronic bronchitis, which together accounted for 25 % of readmissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 304 readmissions, the median (IQR) time to readmission was 11 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) days. The most common readmission diagnoses by CCS Level 3 category were congestive heart failure, pneumonia, coronary atherosclerosis without acute myocardial infarction, cardiac dysrhythmias, and obstructive chronic bronchitis, which together accounted for 25 % of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, readmission might trigger a review of the treatment plan and goals of care. Among discharged older adults, a validated prognostic index is available that stratifies oneyear mortality risk as low, intermediate, or high 11 ; a similar assessment tool for the patients who are readmitted might help inform their care.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] As a result, medical treatment guidelines are increasingly based on prognostic information rather than on arbitrary agebased cutoffs. [8][9][10][11] In addition, prognosis impacts the likelihood of benefits and harms arising from tests or treatments with up-front harms and delayed benefits, such as cancer screenings 12,13 or medications targeted at risk factor reduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, all available mortality prediction models have been developed using data from a single study, but all from the United States and Western Europe (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which greatly limits their validity for use even in other high-income countries, let alone in the developing countries. For instance, a model developed using data from the Health and Retirement Study (HRS) in the United States showed poor performance when it was applied to older adults in England (18).…”
mentioning
confidence: 99%
“…In addition, a recent meta-analysis concluded that none of the prediction models are ready for use in clinical practice, because their validity has not been tested in other populations (15). Another limitation of the existing prediction models is the need for laboratory tests, which increases the costs and reduces the feasibility of using them in developing countries (10,12,19,20). In addition, most models predict mortality for 5 years and may not be adequate for making decisions about chronic disease care such as cancer screening and treatment that may only affect long-term risk (eg, bisphosphonates) (10,12).…”
mentioning
confidence: 99%